The Barriers to High-Growth Enterprises: What Do Businesses in Africa Experience? - Nwajiuba, Chinyere Augusta; Igwe, Paul Agu; Binuomote, Micheal Olayinka; Nwajiuba, Anulika O.; Nwekpa, Kenneth Chukwuma (European Journal of Sustainable Development, 2020)
This study examines the challenges that micro, small and medium enterprises (MSMEs) face and provide insights on African business environment and entrepreneurial ecosystem. In the context of growth-oriented entrepreneurship, good policies and favourable institutional environments support firms' growth, productivity and development, while adverse formal and informal institutions constrain business development. Secondary data from World Bank Enterprise Survey (WBES) was used to capture barriers to entrepreneurship and high-growth opportunities which include – lack of finance, lack of innovation and technology, low skilled workforce, poor infrastructure, unfavorable regulations and more pervasively corruption. These barriers are evident in the micro, meso and macro environments. These have implications on the unemployment rate, poverty rates and economic growth of the African region. Keywords: Micro, Small and Medium Enterprises; Entrepreneurial Ecosystem; African Entrepreneurship; African Business Environments.